Synthesis of Some Bis-(1,3,4-Oxadiazol-2-yl) Methanes of Biological and Pharamacological Interest - Ranga, B.V.; Sangapure, S.S. (Asian Journal of Chemistry, 2010)
The condensation of malonyl dicarbohydrazide with aldehydes yields malonyl dicarbohydrazones which underwent oxidative cyclization to give bis-(5,5´-disubstituted-1,3,4-oxadiazol-2-yl) methanes. The antibacterial, antifungal, anthelemintic and anitcatatonic activities of these compounds were studied.